Translational research in glioblastoma multiforme: molecular criteria for patient selection. (April 2008) - Rosell, Rafael; de las Peññas, Ramon; Balañña, Carme; Santarpia, Mariacarmela; Salazar, Fernanda; de Aguirre, Itziar; Reguart, Noemi; Villa, Salvador; Wei, Jia; Ramirez, Jose Luis; Molina, Miguel Angel; Ramon y Cajal, Santiago; et al.
In spite of the dismal outcome of glioblastoma multiforme (GBM), we are in a position to provide a ray of hope to patients and families. Methylation of MGMT in tumor occurs in approximately a third of patients and predicts meaningful response and survival to adjuvant radiotherapy plus temozolomide. Limited access to tumor tissue in some patients could be circumvented by examining MGMT methylation in circulating serum DNA, although this approach needs to be validated. Molecular signatures are also promising prognostic and predictive markers, and clinical trials should be carried out to validate their use in the selection of patients for specific targeted therapies. Gene expression by quantitative PCR of key components of these molecular signatures could pave the way for easy identification of different subgroups of patients. Translational clinical trials are warranted in order to detect the subgroups of patients resistant to radiotherapy who may derive benefit from novel therapies, including antiangiogenic drugs.